Analysis Of Profitability On Sustainability Report Disclosure Based On GRI Index - Anindyo PRAMUDITO; Muhammad MUWIDHA; Anna ISROWIYAH (Indonesia Strategic Sustainability, 2022)
This study aims to examine the effect of the sustainability report disclosure that is economic, environmental, and social aspects on the financial performance of Return On Assets (ROA). The Global Reporting Initiative (GRI) G4 Standard is used as a guideline for the disclosure of the sustainability report. The population of this research are natural exploration companies (mining and plantation companies) which are listed in the Indonesia Stock Exchange from 2018-2019. A total of 15 companies from mining companies and plantation companies, become the research sample using purpose sampling technique. This is a descriptive quantitative research using linear regression method as the data analysis. Significant results were obtained for each variable, namely the economic aspect of 41.5%, the social aspect of 39.5%, and the environmental aspect of 27.5%. While the R-square results 58.4%. Referring to the analysis, it can be concluded that all aspects have an effect on profitability and economic aspect is more influential than other aspects. It is suggested that the company should consider sustainability issues in improving the company's financial performance and as information for users of the sustainability report, one of the investors’ consideration in investing their capital.